Acidity regulation for improved activity of Mo/HZSM-5 catalyst in methane dehydroaromatization. (2nd February 2023) - Gan, Yuyan; Lv, Qian; Li, Yanru; Yang, Hua; Xu, Kaiyang; Wu, Lizhi; Tang, Yu; Tan, Li
Graphical abstract: Two methods for controlling zeolite acidity by B/L acidity regulation and external surface passivation. Highlights: Suitable ratio of strong to weak Bronsted acid sites plays a crucial role in the MDA reaction. Surface acidity passivation of ZSM-5 enhances the aromatics selectivity. Encapsulated Mo/HZSM-5@S-1(1.07) shows an excellent MDA performance and catalytic stability. Abstract: The Mo/HZSM-5 is a widely studied bifunctional methane dehydroaromatization (MDA) catalyst, and the acid site of zeolite is essential to the reaction process. In this study, the relationship between acid site control and MDA reaction performance is investigated. The Brønsted/Lewis acid sites have been toned by introducing promoters to the ZSM-5 zeolite. It shows that proper strong Brønsted acid sites are conducive to aromatic formation, while excessive Brønsted acid sites will lead to serious coke deposition. Thus, the MDA catalytic stability is further improved by passivation of partial Brønsted acid sites of Mo/HZSM-5 via coating Silicalite-1 on the catalyst surface. The optimized catalyst shows 95 % aromatic selectivity at initial with only 0.06 h −1 deactivation rate constant. The surface of HZSM-5 is reconstructed after hydrothermal treatment and the surface aluminum content is reduced. Moreover, the Silicalite-1 layer is beneficial to Mo species dispersion for preventing its aggregation and stabilizing the Mo-C active sites.